A computational study of the effect of external heat flux and electric field on the nano-pumping of C20 molecules in carbon nanotubes by molecular dynamics simulation - Yupeng Xie; Mohammed Al-Bahrani; Navid Nasajpour-Esfahani; Dheyaa J. Jasim; Maboud Hekmatifar; Shadi Esmaeili; Fay Fathdal; Salah Hassan Zain Al-Abdeen; Davood Toghraie; Malak Jaafar Ali (Journal of Materials Research and Technology, 2023)
Nano-pump is a breakthrough that allows a tiny pump to transfer mass inside the atomic channels. These nanostructures can be used in various applications, such as drug delivery systems in clinical cases. Carbon nanotube (CNT) performance as a nano-pump sample was introduced here. For this purpose, Molecular Dynamics (MD) approach, and external heat flux/electric field effect on nano-pump performance were reported. Hence, various physical parameters, such as nano-pumping time, potential/kinetic energy, stress and entropy were reported to describe the nano-pumping performance of CNT samples. Technically, nano-pumping performance was detected by fullerene (C20) molecule displacement inside the NT. The MD outputs indicated by the heat flux implemented inside CNT, nano-pumping process effectively occur. The results show that by increasing the heat flux amplitude ratio from 0.1 to 0.5 W/m2, the displacement time of C20 molecule decreased from 7.49 to 6.96 ps. By amplitude enlarging, the kinetic energy of defined sample converged to 5.70014 eV. This procedure caused more atomic collisions inside the NT, and the nano-pumping process occurred in a smaller time. Furthermore, the electric field caused the nano-pumping process to be delayed in modeled systems. Numerically, by increasing the electric field, the nano-pumping process occurred after 7.85 ps. Increasing the electric field decreased the mechanical wave produced via Cu tip oscillation. This evolution caused the atomic force, and stress on the target particle converged to a lesser value, and the lattice stress value of modeled sample reached 2.12662 × 106 bar.